The effect of a virtual reality exergame on handgrip strength and cognitive function in post-stroke patients - Jeanie Dewi Wangsa; Rumaisah Hasan; Wa Ode Sri Nikmatiyah; Yose Waluyo; Husnul Mubarak; Andi Alfian Zainuddin (Physical Therapy Journal of Indonesia, 2025)
Background: More than 60% of stroke patients have chronic neurological impairments that impair hand strength and cognitive function, lowering their quality of life. While virtual reality (VR) exergames have been extensively researched as adjuvant therapies, evidence of their simultaneous effects on motor and cognitive skills is scarce. This study aimed to evaluate the impact of VR exergames on handgrip strength and cognitive function in post-stroke patients. Methods: The study used a randomized controlled trial design with 60 subacute post-stroke patients who were randomly assigned to either the control group, which received conventional care (occupational therapy and physiotherapy), or the intervention group (conventional care plus VR exergame therapy) for eight weeks. This study included first-time stroke patients with onset ≥1 month, mild to moderate hemiparesis (MMT ≥ 3), and hemodynamic stability. Participants with significant spasticity (MAS > 3), aphasia, or uncontrolled comorbidities were excluded. Before, during, and after the intervention, handgrip strength and cognitive function were tested using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). Results: After 8 weeks of therapy, the intervention group showed a significant increase in handgrip strength (+3.9 points, p-value= 0.040) and MoCA-Ina scores (+5 points, p-value= 0.007) compared to the control group. Conclusion: Integrating VR exergames with conventional rehabilitation significantly improves handgrip strength and cognitive function in post-stroke patients compared to traditional therapy alone.